MODERN APPROACH TO THE TREATMENT OF INFLAMMATORY DISEASES OF THE CORNEA USING EYE MEDICINAL COATINGS (literature review) - Zebiniso A. Aslonova; Akmal A. Sydykov; Tatyana V.Gavrilova (Central Asian Journal of Medicine, 2024)
Over the past few years, the use of biocoatings in ophthalmology in various pathologies has yielded tangible results. However, most of them are covered with muscle mass: tissue connection, graft fixation, intraocular fluid retention. The development in appearance with an antibacterial manifestation is underway, which is important for patients with inflammatory eye lesions. Research in the field of imparting biocoatings with additional properties and functions is promising in ophthalmology. Scientific research is being carried out around the world to develop effective methods for treating inflammatory eye diseases and optimizing the use of film biocoatings. The development of polycomposite films with methylene blue for the treatment of inflammatory diseases of the cornea, based on hematological, biochemical and pathomorphological changes based on the results of experimental studies in vivo, is important for the scientific substantiation of the results of evaluating the effect of the drug. developed a coating for the processes of regeneration of the cornea based on the results of local and systemic morphological changes. Scientists of Uzbekistan have developed the concept of the optimal composition and properties of the Novacel ophthalmic film. Ziyo "based on a polycomposite polymer material. The film is characterized by biocompatibility, biodegradability, high sorption activity, vapor permeability, elasticity, strength, antimicrobial properties, absence of cytotoxicity, pyrogenic and toxic effects.